Males' mental health disadvantage: An estimation of gender-specific changes in service utilisation for mental and substance use disorders in Australia. (September 2015) - Harris, Meredith G; Diminic, Sandra; Reavley, Nicola; Baxter, Amanda; Pirkis, Jane; Whiteford, Harvey A
Background: Concerns about low levels of service utilisation for mental and substance use disorders in Australia – especially among males – have prompted targeted help-seeking and stigma-reduction initiatives. Resulting changes in service utilisation according to gender are unknown. We modelled the percentage of Australian males with a mental or substance use disorder who used services each year between 2006–2007 and 2011–2012, and the types of services they used, relative to females. Methods: Twelve-month prevalence of mental and substance use disorders, stratified by gender, was synthesised from existing estimates. The percentage of males and females with these disorders who used mental health services in each year from 2006–2007 to 2011–2012 was modelled from published programme activity data, supplemented by analyses of epidemiological survey data. Uncertainty analysis quantified the effects of sampling error and assumptions on the estimates. Results: Modelling showed a significant increase in the percentage of people with mental or substance use disorders who used services for their mental health – from 32.0% in 2006–2007 to 40.0% in 2011–2012 in males and from 45.1% in 2006–2007 to 54.6% in 2011–2012 in females. Growth was driven largely by uptake of private specialised services – males' use of these services grew by 92.7% and females' by 115.4%. There appeared to be a non-significant decrease in use of general practitioner-only mental health care for males (−17.9%), and a significant decrease in the same for females (−35.1%); however, some assumptions made in the modelling of general practitioner-only care require validation. In 2006–2007, the percentage of females treated was 40.9% higher than for males; in 2011–2012, it was 36.6% greater. Conclusions: Recently implemented initiatives have improved males' likelihood of service utilisation, particularly their use of specialised mental health services. Although the gender gap may have narrowed, improving males' access to services should remain a policy priority.